Deep short-read sequences facilitated identification of seven putative drought tolerance genes in a genome-wide association study in soybean - Parajuli, Atit; Chethri, Ramesh; Saha, Iman; Ngaki, Micheline N.; Ryden, Cecelia; Thompson, Madeline; Xing, Qingfeng; Dong, Liang; Bhattacharyya, Madan K. (Frontiers in Plant Science, 2025)
Drought stress significantly limits soybean yield, especially if it occurs during flowering and early pod development stages. To better understand the genetic mechanisms of drought tolerance in legume soybean, we conducted genome-wide association studies (GWAS) for (i) leaf-flipping and (ii) transpiration traits. A short list of seven candidate drought tolerance genes was generated from 67 GWAS-discovered genes by determining if (i) mutations alter structure and function of candidate genes, (ii) the genes are drought responsive due to mutations in putative cis-acting elements, and (iii) they were shown to contribute towards drought tolerance. We used rainout shelters to ensure drought stress and wearable plant sensors to measure leaf-surface humidity and temperature to determine transpiration rates. From GWAS of 240 soybean accessions for the leaf-flipping trait, we identified three candidate drought tolerance genes: (i) a thaumatin-like protein gene, the tea homologue of which regulates the root hair development and drought tolerance in Arabidopsis, (ii) a chloroplast isopropyl malate synthase gene that plays an important role in root development for drought tolerance; (iii) transcriptionally regulated glycinol 2-dimethyltransferase gene. Investigation of 47 accessions for transpiration rates revealed two candidate transcriptionally regulated drought-responsive genes encoding α-tubulin and phosphoenolpyruvate carboxykinase (PCK). The α-tubulin was shown to control stomatal opening, while PCK improves water retention by closing stomata during drought stress. An uncharacterized DUF1118 containing protein and HAT5 homeodomain-leucine zipper protein could also regulate transpiration during drought stress. In this study, we have demonstrated that short-read sequences and transcriptomic data facilitate identification of strong candidate drought tolerance genes.